Reg-1α Promotes Differentiation of Cortical Progenitors via Its N-Terminal Active Domain - Varilh, Marjorie; Acquatella-Tran Van Ba, Isabelle; Silhol, Michelle; Nieto-Lopez, Francisco; Moussaed, Mireille; Lebart, Marie-Christine; Bovolenta, Paola; Verdier, Jean-Michel; Rossel, Mireille; Marcilhac, Anne; Trousse, Françoise (Frontiers in Cell and Developmental Biology, 2020)
Reg-1α belongs to the Reg family of small, secreted proteins expressed in both pancreas and nervous system. Reg-1α is composed of two domains, an insoluble Ctype lectin domain and a short soluble N terminal peptide, which is released from the molecule upon proteolytic N-terminal processing, although the biological significance of this proteolysis remains unclear. We have previously shown that binding of Reg-1α to its receptor Extl3 stimulates axonal outgrowth. Reg-1α and Extl3 genes are expressed in the developing cortex but their expression decreases in adulthood, pointing to a possible function of this signaling system at the early developmental stages. Here, we demonstrate that recombinant Reg-1α increases migration and differentiation of cultured embryonic rat telencephalic progenitors via the activation of GSK-3b activity. In vivo overexpression of Reg1α by in utero electroporation, has a similar effect, favoring premature differentiation of cortical progenitors. Notably, the N-terminal soluble domain, but not the C-type lectin domain, is largely responsible for Reg-1α effects on cortical neuronal differentiation. We thus conclude that Reg-1α via its proteolytically generated N-terminal domain is required for basic development processes.